Critical Thinking, Bias and Feminist Philosophy: Building a Better Framework through Collaboration - Dalgleish, Adam; Girard, Patrick; Davies, Maree (Informal Logic, 2017)
In the late 20th century theorists within the radical feminist tradition such as Haraway (1988) highlighted the impossibility of separating knowledge from knowers, grounding firmly the idea that embodied bias can and does make its way into argument. Along a similar vein, Moulton (1983) exposed a gendered theme within critical thinking that casts the feminine as toxic ‘unreason’ and the ideal knower as distinctly masculine; framing critical thinking as a method of masculine knowers fighting off feminine ‘unreason’. Theorists such as Burrow (2010) have picked up upon this tradition, exploring the ways in which this theme of overly masculine, or ‘adversarial’, argumentation is both unnecessary and serves as an ineffective base for obtaining truth. Rooney (2010) further highlighted how this unnecessarily gendered context results in argumentative double binds for women, undermining their authority and stifling much-needed diversity within philosophy as a discipline. These are damning charges that warrant a response within critical thinking frameworks. We suggest that the broader critical thinking literature, primarily that found within contexts of critical pedagogy and dispositional schools, can and should be harnessed within the critical thinking literature to bridge the gap between classical and feminist thinkers. We highlight several methods by which philosophy can retain the functionality of critical thinking while mitigating the obstacles presented by feminist critics and highlight how the adoption of such methods not only improves critical thinking, but is also beneficial to philosophy, philosophers and feminists alike.